Genetic and functional analyses implicate the NUDT11, HNF1B, and SLC22A3 genes in prostate cancer pathogenesis. - Grisanzio, C; Werner, L; Takeda, D; Awoyemi, B; Pomerantz, M; Yamada, H; Sooriakumaran, P; Robinson, B; Leung, R; Schinzel, A; Mills, I; Ross-Adams, H; et al. (2012)
One of the central goals of human genetics is to discover the genes and pathways driving human traits. To date, most of the common risk alleles discovered through genome-wide association studies (GWAS) map to nonprotein-coding regions. Because of our relatively poorer understanding of this part of the genome, the functional consequences of trait-associated variants pose a considerable challenge. To identify the genes through which risk loci act, we hypothesized that the risk variants are regulatory elements. For each of 12 known risk polymorphisms, we evaluated the correlation between risk allele status and transcript abundance for all annotated protein-coding transcripts within a 1-Mb interval. A total of 103 transcripts were evaluated in 662 prostate tissue samples [normal (n = 407) and tumor (n = 255)] from 483 individuals [European Americans (n = 233), Japanese (n = 127), and African Americans (n = 123)]. In a pooled analysis, 4 of the 12 risk variants were strongly associated with five transcripts (NUDT11, MSMB, NCOA4, SLC22A3, and HNF1B) in histologically normal tissue (P ≤ 0.001). Although associations were also observed in tumor tissue, they tended to be more attenuated. Previously, we showed that MSMB and NCOA4 participate in prostate cancer pathogenesis. Suppressing the expression of NUDT11, SLC22A3, and HNF1B influences cellular phenotypes associated with tumor-related properties in prostate cancer cells. Taken together, the data suggest that these transcripts contribute to prostate cancer pathogenesis.